Sexual Dimorphism in Wax Secretion Offers Ecological Adaptability During Ericerus pela (Hemiptera: Coccidae) Evolution. Issue 2 (13th February 2019) - Qi, Qian; Lv, Pin; Chen, Xiao-Ming; Chen, Hang; Chen, Ming-Shun; Yang, Pu
Abstract: The scale insect, Ericerus pela Chavannes, shows a typical sexual dimorphism. Males and females are different not only in morphology, but also in their ability to secrete wax and ecological adaptability. Here we report the morphological and structural characteristics of wax glands on E. pela females and males. The differences in wax glands and wax secretion between females and males reflect their different needs for living habitats and different ecological strategies. Sciophilous male nymphs are with five types of wax glands, and the wax glands on the dorsum secrete a layer of wax filaments plausibly for protection against direct light irradiation. On the other hand, five types of wax glands were found on the abdomen of females. Heliophilous female nymphs hardly secrete any wax, but the wax glands located along the spiracle on the abdomen may help this insect to breathe. Female adults secrete wax filaments on eggs to protect them from predators and prevent themselves from sticking to each other. In summary, males appear to secreted wax for creating a shaded niche that fits their sciophilous life style, whereas females are likely to adopt an ecological strategy with thickened epidermis for heliophilous acclimatization and overwintering.